The principles governing 'place of effective management' and 'permanent establishments' and their application to the digit al economy: a South African perspective - Boel, Katherine (My University, 2016)
The purpose of this research report is to consider the application of existing 'place of effective management' (POEM) and 'permanent establishment' (PE) principles to a company operating in a digital economy in order to determine its appropriateness and limitations. This paper is broadly divided into four parts. The first part of the paper provides a brief background to the above taidng principles and the digital economy. The second part considers, in detail, the guidance and factors that are currently available on how the POEM and the creation of a PE for a company may be determined both internationally and from a South African tax perspective, including the role of the residency tie-breaker article and the PE article in most double taxation agreements (DTA's) with South Africa. The third part of the paper considers how these guidelines and factors may apply to the digital economy and the practical challenges which arise. Finally, the paper seeks to identify possible alternatives to overcome the pitfalls in the POEM and PE interpretations and to highlight aspects which require further consideration.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Taxation) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2015
Keywords: Place of effective management; The Organisation for Economic Cooperation and Developmet; Key management and commercial decisions; UCTD; SDG-8: Decent work and economic growth